IMPROVING STUDENTS’ COMPREHENSION OF MATHEMATICAL RESEARCH ARTICLES THROUGH CLASS PRESENTATIONS (A Classroom Action Research Study) - Efendi, Ali Satri; Budiasningrum, Retno Setya; Setiawan, Jajang; Suhardianto, Suhardianto (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
ABSTRACT The difficulty in comprehending mathematical research articles written in English remains a common issue among university students, particularly pre-service teachers, due to limited exposure to academic texts. This condition often restricts their ability to connect theoretical understanding with current research practices in mathematics. This classroom action research aimed to enhance students’ comprehension of mathematical research articles through active and reflective class presentations. The study involved 20 third-semester students of the Mathematics Education Study Program at STKIP Kusuma Negara and was carried out in two cycles consisting of planning, action, observation, and reflection stages. The first cycle emphasized understanding the structure and content of articles through presentations, while the second focused on deeper analysis supported by guided reading, terminology clarification, and lecturer feedback. Data were collected through pre- and post-tests, classroom observations, and individual presentations assessments. The findings indicated a significant improvement in students’ ability to understand research structures, methods, and mathematical arguments, with comprehension increasing by 20.0% after Cycle I and 18.1% after Cycle II. It can be concluded that integrating class presentation within a classroom action research framework effectively enhances students’ academic literacy, analytical skills, and confidence in critically understanding and communicating mathematical research articles. ABSTRAK Kesulitan dalam memahami artikel penelitian matematika berbahasa Inggris masih menjadi kendala umum di kalangan mahasiswa, terutama calon guru, karena terbatasnya paparan terhadap teks akademik. Kondisi ini menghambat kemampuan mereka dalam menghubungkan teori dengan praktik penelitian terkini di bidang matematika. Penelitian tindakan kelas ini bertujuan untuk meningkatkan pemahaman mahasiswa terhadap artikel penelitian matematika melalui kegiatan presentasi kelas yang bersifat aktif dan reflektif. Penelitian dilakukan terhadap 20 mahasiswa semester ketiga Program Studi Pendidikan Matematika di STKIP Kusuma Negara melalui dua siklus yang mencakup tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Siklus pertama berfokus pada pemahaman struktur dan isi artikel melalui presentasi, sedangkan siklus kedua menekankan analisis yang lebih mendalam melalui pembacaan terarah, klarifikasi istilah, serta umpan balik dosen. Data dikumpulkan melalui pra-tes dan pasca-tes, pengamatan kelas, serta penilaian presentasi individu. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam kemampuan mahasiswa memahami struktur, metode penelitian, dan argumen matematika dengan peningkatan sebesar 20,0% pada Siklus I dan 18,1% pada Siklus II. Simpulan menunjukkan bahwa integrasi kegiatan presentasi dalam pembelajaran berbasis penelitian tindakan kelas efektif dalam meningkatkan literasi akademik, keterampilan analitis, serta kepercayaan diri mahasiswa dalam memahami dan mengomunikasikan isi artikel penelitian matematika secara kritis dan terarah.